Public health, war and cross-border challenges: the recent cVDPV2 polio outbreak in Gaza - Itamar Grotto; Hazem Agha; Ahmad Abu Al-Halaweh; Nadav Davidovitch; Martin McKee; Dorit Nitzan (EClinicalMedicine)
Summary: The recent vaccine-derived poliovirus type 2 (cVDPV2) outbreak in Gaza, linked to strains circulating in Egypt, highlights the challenges of maintaining vaccination efforts in conflict zones. Amid prolonged hostilities and a deteriorating healthcare system, vaccination coverage has significantly declined, leaving many children vulnerable to poliovirus and other preventable diseases. This report analysed the outbreak's context, vaccination strategies, and outcomes by reviewing vaccination coverage data, environmental surveillance reports, and public health interventions. It focused on the novel oral polio vaccine type 2 (nOPV2) campaigns and their effectiveness in mitigating transmission. The outbreak, detected in June 2024, included six environmental samples and one confirmed case of poliomyelitis in a 10-month-old child. Despite operational challenges, a vaccination campaign immunised 560,000 children under 10 years by September 2024. However, ongoing violence delayed subsequent rounds of vaccination, particularly in northern Gaza. Contributing factors included vaccine hesitancy, logistical hurdles, and the safety risks healthcare workers face. Regional collaboration remains limited despite cross-border transmission risks. The Gaza outbreak illustrates the critical need for robust vaccination programs, enhanced surveillance, and international cooperation to prevent poliovirus resurgence. Addressing vaccine hesitancy and logistical challenges is vital. Sustained funding and innovative strategies, including nOPV2 use, are essential to combat outbreaks in fragile settings and advance global eradication efforts. Funding: No additional funding was used in the preparation of this report.